2021
DOI: 10.1177/15248399211002831
|View full text |Cite
|
Sign up to set email alerts
|

Developing Culturally Tailored mHealth Tools to Address Sexual and Reproductive Health Outcomes Among Black and Latina Women: A Systematic Review

Abstract: Background In addressing the sexual and reproductive health (SRH) disparities for Black and Latina women, there is a need for the development of innovative programs, framed using theoretical underpinnings that are culturally and contextually tailored so that they align with lived experiences. Mobile health (mHealth) interventions offer considerable potential as a means of providing effective SRH education and services. However, there has been a lack of research assessing culturally and contextually tailored mH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Samples were also drawn more frequently from college/university student populations than from any other sampling frame, making our summary estimates unlikely to represent the diverse demographics that exist within countries. Though there is evidence, both from our own results and from past reviews (e.g., Chandler et al, 2022;Huang & Garcia, 2018;Wadi et al, 2022), that motivational matching can be effective for underserved populations within countries, most of this data comes from the aforementioned overrepresented countries (e.g., the United States), and the benefits of motivational matching could vary across groups (e.g., we found smaller effects for at risk populations; Figure 9). Increasing efforts to conduct research with diverse samples may, over time, provide correctives to these limitations of the literature.…”
Section: Strengths and Limitations Of The Current Synthesismentioning
confidence: 56%
“…Samples were also drawn more frequently from college/university student populations than from any other sampling frame, making our summary estimates unlikely to represent the diverse demographics that exist within countries. Though there is evidence, both from our own results and from past reviews (e.g., Chandler et al, 2022;Huang & Garcia, 2018;Wadi et al, 2022), that motivational matching can be effective for underserved populations within countries, most of this data comes from the aforementioned overrepresented countries (e.g., the United States), and the benefits of motivational matching could vary across groups (e.g., we found smaller effects for at risk populations; Figure 9). Increasing efforts to conduct research with diverse samples may, over time, provide correctives to these limitations of the literature.…”
Section: Strengths and Limitations Of The Current Synthesismentioning
confidence: 56%
“…Inequities according to age may be inferred by the confounding effect of this variable on contraceptive use outcomes (table 3). Using multiple social media platforms, language translations and an in-depth co-design process22 23 may have improved the reach, relevance and effectiveness of the intervention for different population groups, including those born outside of Australia who were underrepresented among our participants. However, these strategies would not reasonably mitigate systemic barriers to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Media programs should consider incorporating peers and local community members to speak to the needs and experiences of the target audience, as their participation can also lead to designing more relatable, and in effective, impactful interventions. 60 63 For example, in a recent literature review of culturally and contextually mobile health sexual and reproductive health interventions for Black and Latina women the authors concluded that we need to create programs that are “culturally and contextually tailored so that they align with lived experiences.” 64 The authors go on to explain that, when interventions that are developed with these components in mind, they can offer promising solutions in providing content to those who otherwise would not have access to such information.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63] For example, in a recent literature review of culturally and contextually mobile health sexual and reproductive health interventions for Black and Latina women the authors concluded that we need to create programs that are "culturally and contextually tailored so that they align with lived experiences." 64 The authors go on to explain that, when interventions that are developed with these components in mind, they can offer promising solutions in providing content to those who otherwise would not have access to such information. Second, we aimed to amplify functional social support using a relatable form of digital technology with a goal to influence adolescent sexual behavior.…”
Section: Discussionmentioning
confidence: 99%